Systematic theology ; v. 2 biblical, historical and evangelical - Garrett, James Leo (Grand Rapids, MI Eerdmans, 1995)
Includes bibliographical references and indexes.
Keywords: Christian life; Doctrine (theology).; Jesus Christ -- person and offices